(untitled) (Bioagro, 2024)
After three decades of acting as Editor-in-Chief of Bioagro, I finally decided to step down. I participated in the Editorial Committee of the journal since 1993, and then assumed direction from 1995. I am succeeded in this position by Dr. Rita Ávila, who has a recognized career in the field of scientific research and has maintained an active very fruitful in recent years as a member of the Editorial Committee. I am sure that her high intellectual capacity and dedication will allow her to maintain, or better yet, exceed, the high-quality standards achieved by the journal. In the initial years of running Bioagro it was necessary to overcome the different obstacles that arose while we acquired the necessary experience given that, in university studies, as far as I know, there are no undergraduate or postgraduate courses aimed at training editors of scientific journals. A brief historical account indicates that starting in 1995 the journal achieved complete regularity and stabilization in the quarterly periodicity of its editions, with publication on the first day of January, May and September, as well as its incorporation into the Registry of Publications of the National Fund for Science and Technology (FONACIT) of Venezuela. In 2003 we created the journal website, which currently makes the entire collection available to users (volumes 1 to 36), allowing full-text articles to be freely downloaded. Starting in 2007, it was recognized as a Type A Publication by FONACIT, and in the evaluation of merits carried out by said institution it was ranked among the two most prestigious Venezuelan journals in the agronomic area. In 2012 Bioagro entered the Elsevier Scopus index in the Q3 quartile, and in 2016 it entered the central core of journals of the Web of Science (WoS) through its Science Citation Index (SCI), currently with an impact factor of 0.80 according to the Journal Citation Report (JCR). With this entry, the journal completed its indexing in these two databases, considered as the most recognized worldwide. In previous years, its inclusion in the two most relevant bibliometric indexes in Latin America (Scielo and Redalyc) had already been achieved, as well as its permanence in the Latindex catalogue. In 2018, the Ibero-American Journal Network (REDIB) placed it in the Q1 quartile, occupying first place among the agronomic journals in the region (https://redib.org/Ranking/Revistas?lng=es), while the Scopus evaluation the following year placed Bioagro in first place as the journal with the greatest impact among all areas of knowledge in the country (https://www.scimagojr.com/journalrank.php?country=VE). In recent years, the physical production of the journal was only possible while the paper and other supplies necessary for its printing could be found on the market. This is why in 2018 Bioagro had to change the printed format to digital format, replacing its traditional ISSN 1316-3361 with the new e-ISSN 2521-9693. The international circulation of the printed journal allowed us to expand borders and strengthen ties between the parent institution – the Universidad Centroccidental Lisandro Alvarado – and the academic world, while also obtaining, through the exchange modality, different collections of foreign journals of their genre that went to expand the shelves of the institution’s libraries. Until 2024, Bioagro has published a total of 106 issues belonging to 36 volumes. The rigorous selection and refereeing that the manuscripts received has allowed the publication of approximately 30 % of these manuscripts considering the last five years. Finally, I must emphasize that the Editor must provide the scientific community with clear, concise and timely information. Therefore, adherence to the code of ethics established by the Publications Ethics Committee (COPE) will be maintained in order to guarantee the rigor and scientific quality of the journal, as well as the strict application of the anti-plagiarism policy, and faithful monitoring of Spanish grammar in its editions. Among future expectations, the effective use of the new possibilities offered by digital technology is contemplated, such as continuous publication, content and interactive links, such as videos and audios, which allow users to obtain a better and more dynamic experience of the publications. And knowing that Bioagro is in good hands, I wish for the success of the journal’s new board.